The Effect of Health Insurance Ownership, Travel Time, and Transportation Costs on the Use of Health Facilities by Stunted Toddlers in North Sumatera Province - Syafrina Ulfah; Lubis, Fithri Handayani; Manullang, Hengki Frengki (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
One of the causes of stunting is limited access to health care and essential services. Based on SKI 2023 data, there are still stunted toddlers in North Sumatera who have not used healthcare facilities in the past year since the survey was conducted. The purpose of this study was to analyze the determinants of healthcare facilities utilization in stunted toddlers in North Sumatera, focusing on the factors of health insurance ownership, travel time, and transportation costs. The study design used was cross-sectional with a sample size of 801 stunted toddlers aged 24-59 months in North Sumatera. Univariate data analysis was performed by presenting the results in the form of frequency tables, bivariate analysis using chi-square, and multivariate analysis using logistic regression. Based on the results of bivariate analysis using the chi-square test, it was found that there was no effect of health insurance ownership (p=0.059) and travel time (p=0.108), and there was an effect of transportation costs (p=0.001) on the use of healthcare facilities. Multivariate analysis using logistic regression showed that the variable of transportation costs (p=0.001) had a significant effect on the use of healthcare facilities with an Odd Ratio (OR) value of 3.894. This shows that transportation costs are still a barrier to accessing health care, especially for stunted toddlers. Therefore, a service approach through home visits could be a potential solution so that high transportation costs no longer become a barrier to accessing health services.